1989
DOI: 10.1148/radiology.171.3.2541463
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric breast tissue.

Abstract: A prospective study was undertaken to evaluate the significance of asymmetric breast tissue (asymmetric volume of breast tissue, asymmetrically dense breast tissue with preserved architecture, or asymmetrically prominent ducts) on mammograms. Of 8,408 mammograms obtained in 1985, 221 (3%) demonstrated asymmetric breast tissue. Follow-up was 36-42 months after the initial mammographic study. During this time none of the patients underwent biopsy on the basis of mammographic findings, although 20 underwent excis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 0 publications
2
13
0
2
Order By: Relevance
“…1,2 A study investigating breast density patterns on x-ray mammograms reported symmetry between 30 women's left and right breasts using both subjective and objective measurements schemes. 3 Subjective measures of symmetry were performed by radiologists grading the percentage of dense breast tissue in six categories (none, 0% to 10%, 10% to 25%, 25% to 50%, 50% to 75%, 75% to 100%) and comparing the grade given for right and left breast mammograms.…”
Section: Bilateral Breast Symmetry In X-ray Imaging and Thermographymentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 A study investigating breast density patterns on x-ray mammograms reported symmetry between 30 women's left and right breasts using both subjective and objective measurements schemes. 3 Subjective measures of symmetry were performed by radiologists grading the percentage of dense breast tissue in six categories (none, 0% to 10%, 10% to 25%, 25% to 50%, 50% to 75%, 75% to 100%) and comparing the grade given for right and left breast mammograms.…”
Section: Bilateral Breast Symmetry In X-ray Imaging and Thermographymentioning
confidence: 99%
“…[4][5][6] However, when asymmetric appearance is found between right and left x-ray mammograms, it is considered to be a potential marker for cancer and it is carefully assessed by radiologists. In a study of over 8000 mammograms, it has been reported that only 3% of the cases were assessed by radiologists to have asymmetric breast tissue, 2 which indicates the high amount of similarity often seen between two breasts' mammographic appearances. This study did include asymptomatic and symptomatic women, however, any mammograms found with masses, microcalcifications, or architectural distortions were omitted from the analysis.…”
Section: Bilateral Breast Symmetry In X-ray Imaging and Thermographymentioning
confidence: 99%
See 1 more Smart Citation
“…However, differences in imaging techniques and positioning, weight loss, hormone replacement therapy, or surgical procedures could cause global asymmetry. Occasionally, it may indicate the presence of an underlying breast cancer if it corresponds to a palpable abnormality (Fig 17) (12). In this clinical setting, the radiologist should recall the patient for additional imaging evaluation (Fig 7).…”
Section: Global Asymmetrymentioning
confidence: 99%
“…For example, the original suggestion that asymmetric breast tissue and asymmetrically prominent ducts were a secondary sign of malignancy was based on anecdote without regard to the denominator of these signs among " normal" women. For many years it was believed, on the basis of a few multicase reports, that these features were a secondary sign of malignancy, It was not until a prospective study was performed that it became apparent that asymmetric breast tissue, including asymmetrically prominent ducts, was a normal variation, and it was shown that the prevalence of breast cancer in women with asymmetric breast tissue was essentially no higher than the prevalence in women with symmetric breast tissue [1]. (Fig.…”
Section: And Science In Breast Imagingmentioning
confidence: 99%